PENGARUH FINANCIAL TECHNOLOGY, LITERASI KEUANGAN DAN PRESEPSI RESIKO TERHADAP KEPUTUSAN INVESTASI (Studi Pada Generasi Z Di ITEBIS PGRI Dewantara Jombang) - yanti, Echa Junia Arianti; Rachyu Purbowati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to clarify and examine how risk perception, financial technology, and financial literacy affect investment choices. Data were collected through observation, recording, and distributing questionnaires. Through data collection or samples, this study uses quantitative techniques with a quantitative approach that seeks to characterize or provide an overview of the matter being studied. The population used was ITEBIS PGRI Dewantara Jombang students who invested in stocks in 2024 from a population of 259 customers, researchers only need to take around 157 samples to achieve a 5% error rate. Multiple linear regression analysis, validity and reliability tests, t-tests for hypothesis testing, coefficients of determination (R2), and classical assumption tests were all used in the data analysis process with the help of SPSS. Financial Technology, financial literacy, and risk perception all have a positive and substantial impact on investment decisions, according to the study's findings. Keywords: Financial Technology, Financial Literacy, risk perception, and investment decisions